Some Game via Ἷ-Semi-g-Separation Axioms (Baghdad Science Journal, 2020)
The research demonstrates new species of the games by applying separation axioms via sets, where the relationships between the various species that were specified and the strategy of winning and losing to any one of the players, and their relationship with the concepts of separation axioms via sets have been studied.